Hubungan Pemberian ASI Eksklusif dengan Pertumbuhan Bayi di Puskesmas Jetis Kota Yogyakarta - Nuril Hidayah Asdiningrum; Tri Maryani; Margono - (Sekolah Tinggi Ilmu Kesehatan Akbidyo, 2020)
Background: Growth is affected by internal and external factors. External factor consistof postnatal factor, one of them is nutrition including breastmilk. Nutritional elementsbecome the most dominan influence in children’s growth, especially in early life up to 12month. The coverage of Exclusive Breastfeeding (EBF) in Jetis Public Health Center are77,11%, but the prevalence of fat toddler and skinny toddler also high (9,82% and8,02%).Objective: Knowing the association of EBF and baby’s growth in working area ofPuskesmas Jetis.Method: This study was an observational with crossectional design. This studyconducted in May 2019. Sample were 59 babies aged 6-9 months old. Samplingtechnique used was purposive sampling. Data analysis using chi square with alpa 0,05.Result: Among 44 babies who got exclusive breastfeed, 97,7% of them experiencenormal growth. While among 15 babies who didn’t get exclusive breastfeed, 66,7% ofthem experience normal growth. From chi square test obtained significant result betweenEBF and baby’s growth with p value=0,003, RP=1,4 with CI 95% (1,022-2,103).Conclution: EBF increase the normal growth of babies aged 6-9 months old in JetisPublic Health Center area by 1,4 times. Keywords: relationships, exclusive breastfeeding, growth